Vulvar Verruciform Xanthoma: A Comprehensive Literature Review - Wu W; Sun L; Lu J; Yang X; Liu Q; Wang J (Dove Medical Press, 2022)
Weiwei Wu,1,* Lengbing Sun,2,3,* Jiejie Lu,2 Xianxu Yang,2 Qiao Liu,3,4 Junzhi Wang5 1Department of Plastic and Dermatological Surgery, The Fifth People's Hospital of Hainan Province, Haikou, People's Republic of China; 2Department of Dermatology, The Fifth People's Hospital of Hainan Province, Haikou, People's Republic of China; 3School of Clinical Medicine, Jiangxi University of Chinese Medicine, Nanchang, People's Republic of China; 4Department of Dermatology,The Second Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang, People's Republic of China; 5First Affiliated Hospital of Heilongjiang University of Traditional Chinese Medicine, Harbin, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiao Liu; Junzhi Wang, Email drliuqiao@163.com; drvolodia@163.comAbstract: Verruciform xanthoma (VX) is a rare, benign, mucocutaneous, verrucous, papillary lesion. This paper retrospectively summarizes clinical and pathologic features of 32 vulvar verruciform xanthoma reported from China and abroad. The skin lesions are generally single, mainly in labia minora, clitoris and fourchette with partly extending to the groin, buttocks and anus. The possible inducing factors include long-term scratching, local itching, severe lymphedema or lymphangioma circumscriptum. Severe cutaneous trauma and chronic inflammation may be the main causes. Clinically, it can easily be misdiagnosed as condylomata acuminata, squamous cell carcinoma, bowenoid papulosis, etc. It is reported to be related to underlying disorders. The main treatment is complete resection.Keywords: verruciform xanthoma, vulvar, clinical features, immunohistochemistry, treatment, etiology